2021
DOI: 10.1007/978-3-030-64569-4_26
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Changes in Residential Segregation in São Paulo in the 2000s

Abstract: Residential segregation is known as one of the most prevalent problems of Latin American and Brazilian cities. This chapter looks into the changes in segregation levels in the Metropolitan Region of São Paulo between 2000 and 2010. This period was marked by economic growth and decreasing social inequalities in Brazil with consequent improvement to the quality of life of lower income classes. Despite those improvements, general patterns of urban segregation in Brazilian cities showed remarkable stability, albei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
0
5
0
9
Order By: Relevance
“…These studies used similar spatial scales to promote comparability of results. A more recent series of studies confirmed increasing segregation trends in the already highly segregated São Paulo (Feitosa et al 2021) and in Lima (Fernández-de-Córdova et al 2021), found a decrease of segregation because of greater educational attainment combined with little residential mobility in Mexico City (Monkkonen, Giottonini, and Comandon 2021), and reported persistently high segregation levels (despite sustained economic growth and recovery after the 2001 crisis) in Buenos Aires (Molinatti 2021).…”
Section: Introductionmentioning
confidence: 87%
“…These studies used similar spatial scales to promote comparability of results. A more recent series of studies confirmed increasing segregation trends in the already highly segregated São Paulo (Feitosa et al 2021) and in Lima (Fernández-de-Córdova et al 2021), found a decrease of segregation because of greater educational attainment combined with little residential mobility in Mexico City (Monkkonen, Giottonini, and Comandon 2021), and reported persistently high segregation levels (despite sustained economic growth and recovery after the 2001 crisis) in Buenos Aires (Molinatti 2021).…”
Section: Introductionmentioning
confidence: 87%
“…Da primeira geração de medidas, cabe destacar o pioneirismo e influência contínua até os dias atuais. Essa influência se dá, tanto na condução de análises baseadas nos índices originais (Feitosa et al, 2021;Marques, 2014;Telles, 1992;Torres, 2004, entre outros), quanto no desenvolvimento e uso de medidas da segunda e terceira gerações construídas a partir dos índices pioneiros Feitosa et al, 2007;Lisboa, 2022;S. Lisboa & Feitosa, 2018;Netto et al, 2015Netto et al, , 2018 A emergência dos índices da primeira geração, que atendiam às necessidades de estudos de segregação motivados pelo efervescente movimento dos direitos civis dos negros nos Estados Unidos, buscavam comparar níveis de segregação racial entre cidades ou regiões.…”
Section: Reverberações Das Três Gerações De íNdices No Contexto Brasi...unclassified
“…This new and complex spatial distribution pattern of segregation is described as a "patchwork" that rich and poor intersperse in urban and suburban areas (Florida & Adler, 2018). In some cities in other countries, high-class groups concentrated in the well-serviced city centre, whereas lower-class groups concentrated in remote poor-serviced areas (Feitosa et al, 2021;Korsu & Wenglenski, 2010;Östh et al, 2018;Shen & Xiao, 2020). Studies in Latin America have observed changes in the macro-segregation structure as a consequence of neoliberalism, economic transformation and globalisation (Thibert & Osorio, 2014).…”
Section: Spatial Patterns: From Core-periphery To Patchwork and Mosaicmentioning
confidence: 99%
“…The suburbanisation of wealthy classes has resulted in the emergence of small communities of wealth, such as gated communities (Feitosa et al, 2021). As a result, cities are becoming more fragmented and manifest mosaic at the micro-scale (Brown & Chung, 2006).…”
Section: Spatial Patterns: From Core-periphery To Patchwork and Mosaicmentioning
confidence: 99%